Devolution and Patient Choice: Policy Rhetoric versus Experience in Practice - David Hughes (Social Policy & Administration, 2012)
Background: market reforms in England have been identified as making a clear distinction between English health policy and health policy in the devolved systems in Northern Ireland, Scotland and Wales. Patient choice is a high profile policy in the English National Health Service that constitutes significant changes to the demand side of health care. It is not clear what national differences this has led to regarding implementation of policy. This article presents the findings from a large UK-wide study on the development and implementation of policies related to patient choice of provider. The findings reported here relate specifically to the policy development and organizational implementation of choice in order to examine the impact of devolution on health care policy.Aim: this study examines patient choice of provider across all four countries of the UK to understand the effect of differences in national policies on the organization and service how choice of provider presented to patients.Methods: at the macro-level, we interviewed policymakers and examined policy and guidance documents to analyze the provenance and determinants of national policy in each UK nation. At the Primary Care Trust or Health Board level, we interviewed a range of public and private health service providers to identify the range of referral pathways and where and when choices might be made. Finally, we interviewed ear, nose and throat, and orthopaedics patients to understand how such choices were experienced.Findings: while we found that distinct rhetorical differences were identifiable at a national policy level, these were less visible at the level of service organization and the way choices were provided to patients.Conclusion: historical similarities in both the structure and operation of health care, coupled with common operational objectives around efficient resource use and waiting times, mediate how strategic policy is implemented and experienced in the devolved nations of the UK